Equivalência de estímulos com procedimentos combinados e consciência fonológica na aquisição da leitura generalizada - CAMELO, Mislene Lima (Universidade Federal do Pará, 2011)
Equivalence class formation among pictures and spoken and printed words promotes reading with comprehension, but it does not establish the discriminative control by all the units of the word (letters and syllables). The application of combined special procedures (copy, dictation and oralization - fluently and spelled) while the teaching the conditional relations between dictated words and printed words (AC) favors the establishment of discriminative control by units smaller than the word and the textual and comprehensive reading of the words formed by recombination of those units. The explicit training of syllabic discriminations has been adopted as one of the procedures in the studies on phonological consciousness, with satisfactory results in reading tests. The purpose of the present was to investigate the effect of the two procedures on the acquisition of recombinative reading in preschool children. Three children were exposed to the equivalence and combined special procedures during the acquisition of AC relations (with the words MALA, PATO and BOCA), and four to the explicit training of syllabic discriminations in tasks of rhyme, alliteration, addition and subtraction of syllables, and graphosyllabic correspondence. After a Pre-test, participants of the first group were exposed to the test/training of AB relations (spoken words-figures), and then to AC training with combined procedures and, BC (figures - printed words) and CB tests. During AC training each trial of this relation was followed by a trial of combined procedures of spelled copy, dictation and oralization, and other fluent trial. After the emergence of equivalence relation (BC/CB), children were tested on textual reading of syllables, trained- and generalized- words (formed by the recombination of the syllables of training words). When participants performance reached the minimum of 90% of accuracy in generalized reading test, in the next day a Post-test was carried out. Otherwise, the same procedure was applied again with three generalization words (BOLA, LAMA, and CAPA). The children of the second group were initially exposed to tasks of syllabic recognition and then to tasks of rhyme, alliteration, addition and subtraction of syllables, and graphosyllabic correspondence (with syllables MA, LA, PA, TO, BO, and CA). The participant was only exposed to the training of another syllable if his/her performance reached 100% of accuracy in the task of graphosyllabic correspondence and in the experimental items of the other activities. In the next day, after the conclusion of this training phase, the Pos-test was carried out: three participants of the equivalence group and one of the phonological consciousness presented recombinative reading of some words, but none of them presented generalized recombinative reading. It is suggested that other variables may have interfered in the participants performance: the pre and extra-experimental history, the acquisition of code-related concepts (e.g. left-to-right reading) and the number of training trials. It is also suggested that, when teaching Portuguese reading skills, the combination stimulus equivalence procedures and syllabic discrimination / correspondence is an efficient method to teach recombinative reading. It is proposed that new studies evaluate the effects of the combination of these procedures in the teaching of reading skills.